A DP-like transcription factor protein interacts with E2fl1 to regulate meiosis in Tetrahymena thermophila - Zhang, Jing (Cell Cycle, 2018)
Evolutionarily conserved E2F family transcription factors regulate the cell cycle via controlling gene expression in a wide range of eukaryotes. We previously demonstrated that the meiosis-specific transcription factor E2fl1 had an important role in meiosis in the model ciliate Tetrahymena thermophila. Here, we report that expression of another E2F family transcription factor gene DPL2 correlates highly with that of E2FL1. Similar to e2fl1Δ cells, dpl2Δ cells undergo meiotic arrest prior to anaphase I, with the five chromosomes adopting an abnormal tandem arrangement. Immunofluorescence staining and immunoprecipitation experiments demonstrate that Dpl2 and E2fl1 form a complex during meiosis. We previously identified several meiotic regulatory proteins in T. thermophila. Cyc2 and Tcdk3 may cooperate to initiate meiosis and Cyc17 is essential for initiating meiotic anaphase. We investigate the relationship of these regulators with Dpl2 and E2fl1, and then construct a meiotic regulatory network by measuring changes in meiotic genes expression in knockout cells. We conclude that the E2fl1/Dpl2 complex plays a central role in meiosis in T. thermophila.